Timing Matters: Circadian Rhythm in Sepsis, Obstructive Lung Disease, Obstructive Sleep Apnea, and Cancer - Truong, Kimberly K. (Ann Am Thorac Soc, 2016)
Physiological and cellular functions operate in a 24-hour cyclical pattern orchestrated by an endogenous process known as the circadian rhythm. Circadian rhythms represent intrinsic oscillations of biological functions that allow for adaptation to cyclic environmental changes. Key clock genes that affect the persistence and periodicity of circadian rhythms include BMAL1/CLOCK, Period 1, Period 2, and Cryptochrome. Remarkable progress has been made in our understanding of circadian rhythms and their role in common medical conditions. A critical review of the literature supports the association between circadian misalignment and adverse health consequences in sepsis, obstructive lung disease, obstructive sleep apnea, and malignancy. Circadian misalignment plays an important role in these disease processes and can affect disease severity, treatment response, and survivorship. Normal inflammatory response to acute infections, airway resistance, upper airway collapsibility, and mitosis regulation follows a robust circadian pattern. Disruption of normal circadian rhythm at the molecular level affects severity of inflammation in sepsis, contributes to inflammatory responses in obstructive lung diseases, affects apnea length in obstructive sleep apnea, and increases risk for cancer. Chronotherapy is an underused practice of delivering therapy at optimal times to maximize efficacy and minimize toxicity. This approach has been shown to be advantageous in asthma and cancer management. In asthma, appropriate timing of medication administration improves treatment effectiveness. Properly timed chemotherapy may reduce treatment toxicities and maximize efficacy. Future research should focus on circadian rhythm disorders, role of circadian rhythm in other diseases, and modalities to restore and prevent circadian disruption.